Analisis Tafsir Qur’an Surah Al-Isra Ayat 32 dan Jejaring Ayat Tentang Zina: Analysis of the Quranic Exegesis of Surah Al-Isra' Verse 32 and Related Verses Concerning Zina - Nasution, Labib Asshidqy (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The phenomenon of normalizing pre-marital relationships among Muslim youth, including dating practices and "Friends with Benefits" (FWB), has shifted moral boundaries and obscured religious values. This study aims to analyze the Quran’s holistic response to this phenomenon through a thematic exegesis (tafsir maudhu'i) approach. Employing a qualitative library research method, this study compiles and analyzes core verses regarding zina (adultery/fornication), commencing with Q.S. Al-Isra’: 32, along with its network of supporting verses (Q.S. An-Nur: 2-3, 30-31; Q.S. Al-Furqan: 68). The results indicate that the Quran constructs a comprehensive social ethical system to address zina, consisting of three layers: (1) Preventive Measures through the prohibition of "approaching zina" and guarding one’s gaze; (2) Legal Consequences in the form of clear sanctions serving as a deterrent effect; and (3) Socio-Psychological Solutions through the strengthening of piety (taqwa) and self-control. This thematic synthesis reveals that contemporary issues, such as the public display of relationships on social media and the normalization of FWB, are modern manifestations of "approaching zina" against which warnings have been issued. The study concludes that an educational approach based on a comprehensive understanding of the Quran is more effective in building the moral resilience of Muslim youth in the digital era.